IMPLEMENTASI WIRELESS DISTRIBUTION SYSTEM DAN AUTENTIKASI HOTSPOT MENGGUNAKAN RADIUS SERVER DI PT RIMBA MAKMUR UTAMA: Implementation Of Hotspot Wireless Distribution System And Authentication Using Radius Server in PT Rimba Makmur Utama - Walidatush Sholihah; Armand Fadilla (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2021)
ABSTRACTPT Rimba Makmur Utama is located on Jalan Kantin No.8 Kota Bogor. This private business company is engaged in the field of forest restoration on the island of Kalimantan, precisely in the Sampit region. This company's restoration is to save the forest from illegal logging and protect animals from extinction in the forests around the Sampit area. PT Rimba Makmur Utama is already using a hotspot so users can connect to the internet. However, problems arise when users move between rooms or places in the office but the wireless signal coverage cannot be reached. To overcome this, the solution is to build a Wireless Distribution System (WDS) network. WDS is a method that can be used to expand wireless networks by connecting multiple access points without using cables. Hotspot networks do not always provide fast and stable internet access. To overcome this, a user management system and bandwidth are needed using the Remote Authentication Dial In User Service protocol or RADIUS Server. User Manager is a RADIUS Server developed by MikroTik. All the area in the building have been covered with the internet. Users need username and password to connected to the network in the building.